Preclinical Evidence of Nanomedicine Formulation to Target Mycobacterium tuberculosis at Its Bone Marrow Niche - Garhyan, Jaishree; Mohan, Surender; Rajendran, Vinoth; Bhatnagar, Rakesh (Pathogens (Basel), 2020)
One-third of the world’s population is estimated to be latently infected with Mycobacterium tuberculosis (Mtb). Recently, we found that dormant Mtb hides in bone marrow mesenchymal stem cells (BM-MSCs) post-chemotherapy in mice model and in clinical subjects. It is known that residual Mtb post-chemotherapy may be responsible for increased relapse rates. However, strategies for Mtb clearance post-chemotherapy are lacking. In this study, we engineered and formulated novel bone-homing PEGylated liposome nanoparticles (BTL-NPs) which actively targeted the bone microenvironment leading to Mtb clearance. Targeting of BM-resident Mtb was carried out through bone-homing liposomes tagged with alendronate (Ald). BTL characterization using TEM and DLS showed that the size of bone-homing isoniazid (INH) and rifampicin (RIF) BTLs were 100 ± 16.3 nm and 84 ± 18.4 nm, respectively, with the encapsulation efficiency of 69.5% ± 4.2% and 70.6% ± 4.7%. Further characterization of BTLs, displayed by sustained in vitro release patterns, increased in vivo tissue uptake and enhanced internalization of BTLs in RAW cells and CD271+BM-MSCs. The efficacy of isoniazid (INH)- and rifampicin (RIF)-loaded BTLs were shown using a mice model where the relapse rate of the tuberculosis was decreased significantly in targeted versus non-targeted groups. Our findings suggest that BTLs may play an important role in developing a clinical strategy for the clearance of dormant Mtb post-chemotherapy in BM cells.